SIKAP INDONESIA TERKAIT KASUS PENGHINDAR PAJAK: STUDI KASUS INDONESIA-SINGAPURA - Rizka Isti Faricha; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Tax has the highest percentage in the order of income sources of Indonesian state budget. Even though tax revenues in Indonesia can support more than half of the state budget revenue, there are still many tax avoidance which is conducted by Indonesian taxpayers. Within the countries that are listed aimed for the tax amnesty program, Singapore ranked first on the top five positions. This study will explain the internal reasons behind the actions of Indonesia which has chose to implement the tax amnesty policy. Regarding as to why Indonesia chose to implement tax amnesty compared to providing legal sanctions, related to the many cases of tax evasion by Indonesian citizens who hold assets in Singapore.Also to help analyze the above phenomena, the author uses the concept of Foreign Policy Analysis, namely Internal Settings from Richard Synder, Bruck and Sapin. Data was collected using literature review and official government archives. The results showed that internal factors, namely the need for funds to finance government programs, were the driving force for Indonesian government under the leadership of President Joko Widodo to implement the tax amnesty policy and also the dependence of the Indonesian people on Singapore's investment.